Chemical composition and biological activities of essential oil of the Malaysian endemic Syzygium variolosum (King) Chantar. & J.Parn - Wan Mohd Nuzul Hakimi Bin W SalleH (Tanjung Malim, 2024)
Chemical composition and biological activities of essential oil of the Malaysian endemic Syzygium variolosum (King) Chantar. & J.Parn by Wan Mohd Nuzul Hakimi Bin W SalleH